The adrenal gland and primary aldosteronism: anatomy, steroidogenesis, regulation, and genetic insights - Long, Kha Chin; Azizan, Elena Aisha (Frontiers in Endocrinology, 2026)
The adrenal glands play an essential role in maintaining homeostasis through the secretion of steroid hormones. Among these, aldosterone, a mineralocorticoid produced in the zona glomerulosa (ZG) of the adrenal cortex, regulates fluid balance and blood pressure. This review summarizes the current knowledge of adrenal anatomy, aldosterone biosynthesis and regulation, and the pathophysiology and genetic landscape of primary aldosteronism (PA), a common form of secondary hypertension. Advances in next-generation sequencing have enabled the discovery of novel somatic and germline mutations underlying PA, elucidating their roles in abnormal aldosterone production and adrenal cell proliferation. Understanding the molecular basis of aldosterone dysregulation provides critical insights into PA subtypes, informing the development of improved diagnostic and therapeutic strategies.